2007
DOI: 10.1124/mol.107.034413
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Interaction ofBordetella pertussisAdenylyl Cyclase with Fluorescent Nucleotides

Abstract: The calmodulin (CaM)-dependent adenylyl cyclase (AC) toxin from Bordetella pertussis (CyaA) substantially contributes to the pathogenesis of whooping cough. Thus, potent and selective CyaA inhibitors may be valuable drugs for prophylaxis of this disease. We examined the interactions of fluorescent 2Ј,3Ј-Nmethylanthraniloyl (MANT)-, anthraniloyl-and trinitrophenyl (TNP)-substituted nucleotides with CyaA. Compared with mammalian AC isoforms and Bacillus anthracis AC toxin edema factor, nucleotides inhibited cata… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(92 citation statements)
references
References 27 publications
7
85
0
Order By: Relevance
“…Adefovir diphosphate (PMEApp) has been shown to inhibit adenylate cyclase activity of edema factor (EF) and adenylate cyclase toxin (ACT), the key virulence factors of Bacillus anthracis and Bordetella pertussis, respectively (10,11). Although the prodrug bis(POM)PMEA (compound 2, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adefovir diphosphate (PMEApp) has been shown to inhibit adenylate cyclase activity of edema factor (EF) and adenylate cyclase toxin (ACT), the key virulence factors of Bacillus anthracis and Bordetella pertussis, respectively (10,11). Although the prodrug bis(POM)PMEA (compound 2, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Adefovir is currently used for the treatment of chronic hepatitis B virus infection (9). In addition to that, its active metabolite diphosphorylated form PMEA (PMEApp) has been found to inhibit activity of bacterial AC-based toxins, including ACT and edema factor (EF) of Bacillus anthracis (10,11). The crystal structures of ACT and EF in complex with calmodulin and PMEApp have been reported (12).…”
mentioning
confidence: 99%
“…In other studies we have shown that 2Ј(3Ј)-O-MANT-substituted NTPs are moderately potent competitive CyaA inhibitors with K i values in the range of 0.2 to 10 M (Gille et al, 2004;Göttle et al, 2007). CyaA exhibits a broad base specificity for purine and pyrimidine nucleotides (Göttle et al, 2007(Göttle et al, , 2010, indicating that the catalytic site possesses substantial conformational flexibility and is spacious.…”
Section: Introductionmentioning
confidence: 99%
“…CyaA exhibits a broad base specificity for purine and pyrimidine nucleotides (Göttle et al, 2007(Göttle et al, , 2010, indicating that the catalytic site possesses substantial conformational flexibility and is spacious. Figure 1 provides an overview of structures of MANT nucleotides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation